2022
DOI: 10.11124/jbies-22-00022
|View full text |Cite
|
Sign up to set email alerts
|

Wants and needs for involvement experienced by relatives of patients with an acquired brain injury: a scoping review

Abstract: Objective: The objective of this scoping review was to identify and map the breadth of available evidence on relatives’ wants and needs for involvement in the care of patients with an acquired brain injury. Introduction: Acquired brain injuries often occur suddenly and unexpectedly. Experiencing an acquired brain injury has major consequences, not only for the patients—due to the devastating impact on their physical, cognitive, social, and psychological well-being—but also for the relatives who may need to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 99 publications
1
19
0
Order By: Relevance
“…Patients with an MBT face a poor prognosis with an average life expectancy of about 14 months, 34 and the relatives may be more concerned about life expectancy and illness progression. Therefore, we decided to deviate from the protocol and divide the findings into 2 scoping reviews 31 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with an MBT face a poor prognosis with an average life expectancy of about 14 months, 34 and the relatives may be more concerned about life expectancy and illness progression. Therefore, we decided to deviate from the protocol and divide the findings into 2 scoping reviews 31 …”
Section: Methodsmentioning
confidence: 99%
“…To be eligible for inclusion, studies must have referred to the wants and needs of relatives involved in the care of patients with an MBT. The wants and needs for involvement were identified in relation to participating in decision-making concerning treatments, sharing information and knowledge, setting goals, planning the patient’s discharge, and being actively involved in nursing care and exercises, among others 31 …”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Little has been explored about relatives’ needs for involvement in the disease trajectory of patients with ABI or MBT. However, a scoping review has illuminated the need for relatives of patients with ABI to be primarily related to information, communication and support from HCPs, which is important not only in being able to understand the situation, but also to be involved in care and decision-making 10. On the contrary, a scoping review reporting on the wants and needs for involvement of relatives to patients with an MBT identified that relatives were already involved in the disease trajectory but expressed a need for a stronger connection with HCPs because their relatives’ needs changed rapidly as the disease progressed.…”
Section: Introductionmentioning
confidence: 99%
“…If HCPs are able to identify and ultimately meet relatives’ wants and needs for involvement, this might improve their coping, patient satisfaction and high-quality nursing care. HCPs may be able to increase the capacity of relatives in their new role as caregivers if they can identify and use relatives’ wants and needs for involvement in collaboration with their relatives 10…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JBI Evidence Synthesis , we present 2 reviews featuring a translation of the review abstract. “Wants and needs for involvement experienced by relatives of patients with an acquired brain injury: a scoping review” 13 features German and Danish translations, and “Incidence of severe infection in patients with rheumatoid arthritis taking biologic agents: a systematic review” 14 includes a Japanese translation. Both of these abstracts have been translated by members of the author team and are available as supplemental digital content.…”
mentioning
confidence: 99%